2021
DOI: 10.3390/axioms10040319
|View full text |Cite
|
Sign up to set email alerts
|

Torsion for Homological Complexes of Nonassociative Algebras with Metagroup Relations

Abstract: The article is devoted to homological complexes and modules over nonassociative algebras with metagroup relations. Smashed tensor products of them are studied. Their torsions and homomorphisms are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Proof. An existence of φ satisfying condition (23) follows from identities (16)- (22). Similarly, there exists a G-graded homomorphism η : C → C such that η(x⊗ y) = x ⊗ y for each x ∈ X and y ∈ Y.…”
Section: Modules Over Nonassociative Algebras With Metagroup Relationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Proof. An existence of φ satisfying condition (23) follows from identities (16)- (22). Similarly, there exists a G-graded homomorphism η : C → C such that η(x⊗ y) = x ⊗ y for each x ∈ X and y ∈ Y.…”
Section: Modules Over Nonassociative Algebras With Metagroup Relationsmentioning
confidence: 93%
“…Therefore, it is important to develop this area over octonions, Cayley-Dickson algebras, and more general nonassociative algebras with metagroup relations. Examples of nonassociative algebras, modules, and homological complexes with metagroup relations are given in [12,13,23]. In these works, it is shown that generalized Cayley-Dickson algebras are particular cases of metagroup algebras.…”
Section: Introductionmentioning
confidence: 99%